2021
DOI: 10.1371/journal.pone.0251628
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to extremely low-frequency magnetic fields and childhood cancer: A systematic review and meta-analysis

Abstract: Background Extremely low frequency magnetic fields (ELF-MFs) are classified as a possible carcinogenic factor (Group 2B). This study assessed the association between ELF-MFs and childhood cancer through a systematic review and meta-analysis. Methods Three databases were searched in January 2020. We conducted a meta-analysis for the association between the ELF-MFs exposure level and childhood cancer. Results A total of 33 studies were identified. Thirty studies with 186,223 participants were included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Exposure to ELF-MF during childhood was found to have “some” evidence as a risk factor of childhood leukemia. All meta-analyses had summary RR of >1.00 [ 77 , 78 , 79 , 80 , 81 , 82 ], including a recent publication by Seomun et al [ 82 ]. On the contrary, Amoon et al [ 81 ] reported no association in another recent publication.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to ELF-MF during childhood was found to have “some” evidence as a risk factor of childhood leukemia. All meta-analyses had summary RR of >1.00 [ 77 , 78 , 79 , 80 , 81 , 82 ], including a recent publication by Seomun et al [ 82 ]. On the contrary, Amoon et al [ 81 ] reported no association in another recent publication.…”
Section: Resultsmentioning
confidence: 99%
“…Their evaluation was based on a pooled analysis (individual level data) of four studies published between 2015 and 2017 [ 83 , 84 , 85 , 86 ]. These four studies were also in the systematic review of Seomun et al [ 82 ]. Paternal smoking during childhood was found to have “little” evidence as a risk factor of childhood ALL but not maternal smoking in the same exposure window [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have primarily been performed for identifying long-term health impacts, including the causes of pediatric cancer, which have attracted public attention because of the vulnerability of children during their growth period [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, The International Agency for Research on Cancer (IARC) revealed that extremely low frequency (ELF) magnetic fields are 'possibly carcinogenic to humans' [12][13][14][15]. Most of the neural activities in the brain are processed through electrical impulses.…”
Section: Introductionmentioning
confidence: 99%